METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA PADA ANAK KELOMPOK A DI RA NURUR RABIAH KOTA TASIKMALAYA - Iyus Rusmiati; Asep Mumung; Tetin Nurfitri (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2020)
This research is motivated by the fact that there are still many children who experience difficulty in speaking ability based on the achievement of language development that is in the underdeveloped category and is starting to develop. So that innovation is needed in learning methods that are able to improve the ability of speaking in group A children in RA Nurur Rabiah .. This study aims to determine the effect of role playing methods on language skills in group A children in RA Nurur Rabiah. This research is classified as a quasi experiment with a post-test only control group design. The study population was children of group A in RA Nurur Rabiah ... The sample of this study was 14 children of group A as the experimental group, and 14 children of group A1 as a control group. The results showed that there was a significant influence on the role playing method (on the ability to speak in group A children in RA Nurur Rabiah.